Erau Festival: Building Religious Moderation Through Education for Generation Alpha in Kutaikartanegara - Wiwik Angranti; Nur Kholik Afandi; Fathul Jannah (IAIN Palangka Raya, 2025)
The Erau Festival in Kutai Kartanegara is a traditional ritual that represents gratitude and the multicultural local wisdom of the community. This festival has the potential to serve as a bridge for strengthening religious moderation, particularly among the younger generation. This study aims to develop teaching materials based on the values of the Erau Festival, which are aligned with the four pillars of religious moderation, and to examine their implications on students' mindsets and cultural awareness. The research employs the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed teaching materials were implemented and tested in two multicultural schools. Data was collected through observation and interviews, and then analyzed qualitatively. The results indicate a significant increase in cultural awareness, rising from an initial 28% among participants to 58% post-implementation, and the initiative received support from the schools. Furthermore, an observable improvement occurred in social interactions among students. The study concludes that the local wisdom values within the Erau Festival can be transformed into effective teaching materials to instill religious moderation and multicultural awareness in the Alpha generation. The implication of this research provides a practical model for integrating local wisdom into formal education.